Do Domestic Violence Courts Work? A Meta-Analytic Review Examining Treatment and Study Quality. (December 2016) - Gutierrez, Leticia; Blais, Julie; Bourgon, Guy
Domestic violence courts (DVCs) have become an increasingly popular model in the problem-solving court system. To date, there have been no efforts to summarize the extant literature regarding the impact of DVCs on recidivism. The present study is a meta-analysis of 20 DVC outcome studies reporting on 26 unique DVC samples. The results indicated that DVCs are having a positive impact (i.e., lower odds) on general recidivism (odds ratio [ OR ] = .81, 95% CI [0.68, 0.98], k = 18) as well as domestic violence recidivism ( OR = .81, 95% CI [0.67, 0.97], k = 21), compared to domestic violence offenders processed through the traditional court system. These results, however, became nonsignificant when considering studies of sound methodological quality (as assessed by the Collaborative Outcome Data Committee guidelines). The study also conducted a preliminary investigation of treatment quality (adherence to risk, need, and responsivity [RNR] principles) in the DVC literature. The results indicated that adherence to the RNR principles was low but significantly related to greater treatment effects. Future research should aim to increase the quality of evaluation designs and the courts should look to existing offender rehabilitation literature to inform best practices with domestic violence offenders.